Pendidikan Dasar Inklusif di Kabupaten Pati: Harapan dan Kenyataan - Sulthon Sulthon (INKLUSI, 2019)
This study examines the implementation of inclusive elementary education in Pati district. Data collection was carried out through interviews and observations of eight students with disabilities who attended inclusive elementary schools in Pati Regency, 6 teachers, and 3 school principals. Data analysis was performed using data reduction techniques, data presentation, and conclusion drawing. The results of the study indicate that the implementation of inclusive basic education in Pati Regency is not under idealized conditions because in its implementation the school still limits students with disabilities who are accepted. Schools only accept those who have non-physical disabilities (intellectual disability, slow learning, and sensory disabilities). School considerations are: 1) easy in learning services; 2) worry if parents of non-disabled students refuse and move their children to another school; 3) there are obstacles in learning services because they do not have special support teachers and the lack of inclusive learning facilities and infrastructure.[Makalah ini meneliti pelaksanaan pendidikan dasar inklusif di kabupaten Pati. Pengumpulan data dilakukan melalui wawancara dan observasi terhadap delapan siswa difabel yang bersekolah di SD inklusif di Kabupaten Pati, 6 guru, dan 3 kepala sekolah. Analisis data dilakukan dengan menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pelaksanaan pendidikan dasar inklusif di Kabupaten Pati belum sesuai dengan kondisi yang diidealkan karena dalam pelaksanaannya sekolah masih membatasi siswa difabel yang diterima. Sekolah hanya menerima mereka yang mengalami disabilitas non-fisik saja (disabilitas intelektual, lambat belajar, dan disabilitas sensorik). Pertimbangan sekolah adalah: 1) mudah dalam layanan pembelajaran; 2) merasa khawatir jika orang tua siswa non-difabel menolak dan memindahkan anaknya ke sekolah lain; 3) adanya kendala dalam layanan pembelajaran karena tidak memiliki guru pembimbing khusus, dan kurangnya sarana dan prasarana pembelajaran inklusif.]